Productivity analysis of family takaful in Indonesia and Malaysia: Malmquist productivity index approach - Puji Sucia Sukmaningrum; Achsania Hendratmi; Sylva Alif Rusmita; Syadiyah Abdul Shukor (Emerald, 2024)
Indexed by WOS/Scopus/ERA